Chemical and Biological Profile and Allergenicity of Thymus baicalensis Plant of Mongolian Origin - Tuya Narangerel; Michał Sójka; Radosław Bonikowski; Konrad Jastrząbek; Witold Sroczyński; Aleksandra Plucińska; Alina Kunicka-Styczyńska; Krzysztof Śmigielski; Iwona Majak; Adrian Bartos; Joanna Leszczyńska (MDPI AG, 2021)
Thymus baicalensis is a medicinal plant recognized as a traditional Mongolian therapeutic and health-promoting food supplement. The aim of the study was to check the suitability of the tested plant for supporting the treatment of certain diseases. The following study is the first one to showcase the versatile scope of characteristics of T. baicalensis, including its volatile oil composition, polyphenolic composition, lipid composition, phenolic and flavonoid contents, antioxidant activity, antimicrobial properties and ingestive allergenicity. Myrcene, at 26.15%, was shown to be the most abundant component of the volatile oil. Compounds known as inherent components of the Thymus genus: thymol and carvacrol made up only about 0.24% of the extracted oil. As much as 10.11 g kg−1 of polyphenol compounds were identified as derivatives of luteolin-7-O-glucuronide. The lipid extract was found to be rich in palmitic acid (31.05%), while unsaturated fatty acids were not reported. Spectrophotometric determination of the phenols and flavonoids indicated 7.541 mg of gallic acid g−1 and 4.345 mg of quercitin g−1, respectively. The free radical scavenging activity was determined by the 2,2-difenylo-1-pikrylohydrazyl method at IC50 = 206.97 µg mL−1. The extracts also had a strong inhibitory effect on M. flavus and P. fluorescenes bacteria, as well as S. cerevisiae yeasts. The Bet v 1 and profilin allergens in T. baicalensis were reported at 175.17 ng g−1 and 1.66 ng g−1, respectively.